RNA polymerase-dependent mechanism for the stepwise T7 phage DNA transport from the virion into E. coli. - Zavriev, S K (1982)
The influence of rifampicin, streptolydigin, tetracycline and chloramphenicol on phage DNA transport from the T7 virion into the E. coli cell was studied. It has been found that the DNA transport proceeds in at least three stages. During the initial stage the phage injects into the host cell the left approximately 10 per cent of its DNA molecule. The entrance of the next 50 per cent of 17 DNA molecule is blocked by inhibitors which block transcription but not translation. Moreover, the entrance time of this part of the T7 DNA increases in the case of the T7 mutant D111 (which contains a deletion of the A2 and A3 promoters) and decreases in the case of the D53 mutant (which contains a deletion in the region of the early gene transcription terminator). It would appear, that the second stage of the phage DNA transport is tightly coupled with its transcription and that a mechanical function is carried out by RNA polymerase. The translation inhibitors completely block the entrance of the remaining 40 per cent of the 17 DNA molecule (class III genes) into the host cell. It would appear that some class I and (or) II gene product(s) are obligatory components of the final stage of 17 DNA transport. Some probable consequences of this virus DNA transport model as well as its agreement with the functional structure of T7 chromosome and with T7 development are discussed.